An Analysis of Work Discipline, Work Environment and Employment Satisfaction Towards Performance - Nasir, Munawir; Murfat, Moh. Zulkifli; Basalamah, Jafar; Basalamah, Abdurahman (Universitas Muhammadiyah Yogyakarta, 2020)
This study aims to determine whether work discipline, work environment, and job satisfaction have a real and significant impact on the performance of the Makassar Islamic University Academic Office and identify the most important variables affecting the performance of university academic staff. The research method use Analysis method. Data were collected using a list of questions or questionnaires filled out by respondents and then analyzed using multiple linear regression analysis. The results show that labor discipline (Discipline variable1), work environment variable X2 )and job satisfaction variable X3) also significantly demonstrate the performance of employees at the Islamic University Academic Makassar. The variable that has a significant impact on employee performance is the work discipline variable.